PENERAPAN VIDEO TUTORIAL RESTAURANT MISE EN PLACE UNTUK MENINGKATKAN PENGETAHUAN SISWA - Rina Febriana; Yeni Yulianti (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2021)
Abstract Education is one of the focuses in the UNJ PPM Strategic Plan for 2021-2025. To realize a program that focuses on education, this Community Service (P2M) activity applies research technology to be applied to learning at Vocational High Schools (SMK) in the North Jakarta area. This service activity aims to improve learning about cuisine in the Mise En Place Restaurant subject at SMK. P2M is done through the use of Restaurant Mise En Place video tutorial media. The location of the activity was carried out at SMKN 33 Jakarta. The method of data analysis in this activity uses descriptive quantitative methods. The technique of collecting data is through test instruments to measure the effectiveness of activities and questionnaires to measure the satisfaction of activity participants. The results of the P2M activity showed that participants experienced an increase in knowledge of the Restaurant Mise En Place material with an average score of 55.9 and post test 85.9 and P2M participants were satisfied with this activity, seen from the scores obtained through the evaluation of the satisfaction of the questionnaire participants, as many as 83 % said they were very satisfied and 17% said they were satisfied. The material provided can be viewed again via social media youtube. Abstract Pendidikan merupakan salah satu fokus dalam Renstra PPM UNJ tahun 2021-2025. Untuk merealisasikan program pada fokus pendidikan maka kegiatan Pengabdian pada Masyarakat (P2M) ini adalah menerapkan teknologi hasil penelitian untuk diterapkan pada pembelajaran di Sekolah Menengah Kejuruan (SMK) di wilayah Jakarta Utara. Kegiatan pengabdian ini bertujuan meningkatkan pembelajaran Tata Hidang pada pokok bahasan Restaurant Mise En Place di SMK. P2M dilakukan melalui pemanfaatan media video tutorial Restaurant Mise En Place. Lokasi kegiatan dilakukan di SMKN 33 Jakarta. Metode analisis data pada kegiatan ini menggunakan metode deskriptif kuantitatif. Teknik pengumpulan data melalui instrumen tes untuk mengukur efektifitas kegiatan dan kuesioner untuk mengukur kepuasan peserta kegiatan. Hasil kegiatan P2M menunjukan bahwa peserta mengalami peningkatakan pengetahuan pada materi Restaurant Mise En Place dengan nilai rata-rata 55,9 dan post test 85,9 dan peserta P2M merasa puas dengan kegiatan ini, dilihat dari skor yang diperoleh melalui angket evaluasi kepuasan peserta, sebanyak 83% menyatakan sangat puas dan 17% menyatakan puas. Materi yang diberikan dapat dilihat kembali melalui media sosial youtube.